2021
DOI: 10.1002/iub.2467
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Chinese herbal medicine on digestive system and liver functions should not be neglected in COVID‐19: An updated systematic review and meta‐analysis

Abstract: Gastrointestinal symptoms and liver injury are common in patients with coronavirus disease 2019 (COVID‐19). However, profiles of different pharmaceutical interventions used are relatively underexplored. Chinese herbal medicine (CHM) has been increasingly used for patients with COVID‐19, but the efficacy of CHM used in COVID‐19 on gastrointestinal symptoms and liver functions has not been well studied with definitive results based on the updated studies. The present study aimed at testing the efficacy of CHM on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
0
19
0
3
Order By: Relevance
“…24 A meta-analysis showed that the TCM as a complementary therapy for treating COVID-19 may not be beneficial for improving liver function based on the current evidence. 23 In this study, we found that the TCM use is one of the predictors of peak hospitalization ALT > 5 ULN. Based on previous studies and our results, we suggested that prevention and management of TCMinduced liver injury should be concerned in COVID-19 patients who received TCM therapy.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…24 A meta-analysis showed that the TCM as a complementary therapy for treating COVID-19 may not be beneficial for improving liver function based on the current evidence. 23 In this study, we found that the TCM use is one of the predictors of peak hospitalization ALT > 5 ULN. Based on previous studies and our results, we suggested that prevention and management of TCMinduced liver injury should be concerned in COVID-19 patients who received TCM therapy.…”
Section: Discussionmentioning
confidence: 58%
“…Many TCM were used in patients with COVID-19 in our cohort; therefore, the effect of TCM on liver functions should not be neglected in COVID-19 patients. 23 In fact, the TCM-related liver injury is not uncommon in patients with COVID-19. 24 A meta-analysis showed that the TCM as a complementary therapy for treating COVID-19 may not be beneficial for improving liver function based on the current evidence.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, 331 studies were screened by the titles and abstracts, and 32 studies were assessed through the full texts. Finally, 23 SRs were included in this study (Lin et al, 2020;Cai et al, 2020;Fan et al, 2020;Liu M. et al, 2021;Pang et al, 2020;Qi et al, 2020;Sun C. Y. et al, 2020;Xiong et al, 2020;Wang et al, 2020;Wu et al, 2020;Yang et al, 2020;Zhang W. B. et al, 2020;Zhang H. Y. et al, 2020;Gao et al, 2021;Luo et al, 2021;Liu A. H. et al, 2021;Ouyang et al, 2021;Shi et al, 2021;Zeng et al, 2020;Zhou et al, 2021). The literature screening procedure is shown in Figure 1.…”
Section: Literature Selectionmentioning
confidence: 99%
“…The basic characteristics of the included SRs are presented in Table 1. The 23 included SRs were published between 2020 and 2021, with 13 SRs in English (Liu et al, 2020;Cai et al, 2020;Fan et al, 2020;Liu M. et al, 2020;Pang et al, 2020;Sun C. Y. et al, 2020;Xiong et al, 2020;Luo et al, 2021;Shi et al, 2021;Zeng et al, 2020;Zhou et al, 2021) and 6), ( 7), ( 10), ( 11), ( 13), ( 14), ( 18), ( 19), ( 21), ( 30), ( 34), ( 35), ( 36), ( 37), ( 40), ( 41), ( 42), ( 44), (45) 3), ( 8), ( 16), ( 18), ( 19), ( 20), ( 21), ( 22), ( 23), ( 24), ( 27), ( 30), ( 35), ( 36), ( 38), ( 41), ( 45), ( 47), ( 48), ( 49 3), ( 7), ( 30), (…”
Section: Study Characteristicsunclassified
“…In addition, the same author observed that patients with gastrointestinal symptoms had higher levels of liver enzymes, monocytes reduction, and increasement of prothrombin time and received antimicrobial therapy. In these cases, the symptoms improve and the treatment base needs further studies (47) (66).…”
Section: Gastrointestinal Symptomsmentioning
confidence: 99%